A Validated 1H NMR Method for the Quantitation of 5-Hydroxymethyl-2(5H)-Furanone, a Valuable Chemical Intermediate, In a Dichloromethane Extract of Helleborus lividus subsp: Corsicus Leaves from Corsica. (24th August 2022) - Maroselli, Thomas; Paoli, Mathieu; Bighelli, Ange
Abstract : An experimental procedure using 1 H NMR was developed and validated to quantify 5-hydroxymethyl-2(5H)-furanone, a valuable chemical synthon ((S)-enantiomer), in a dichloromethane extract of Helleborus lividus subsp. corsicus leaves. This method, using vanillin as the internal standard, exhibited a perfect linearity of measurements ( R 2  = 1) associated with very good accuracy (relative errors comprised between −1.62% and 4.25%) and precision (reproducibility 30.51 mg ± 0.4%). The limit of detection and the limit of quantitation have been measured at 0.14 mg and 0.59 mg, respectively. The experiment time is very short since a single analysis is at the minute level. 5-Hydroxymethyl-2(5H)-furanone accounted for nearly 85% in the dichloromethane extract of H. lividus subsp. corsicus leaves (1.7% of the mass of fresh leaves). This plant represents an important and natural source of (S)-5-hydroxymethyl-2(5H)-furanone (main enantiomer; determined using a GC chiral analysis).